Effect of Change in Material Properties of the Abradable Coating on the Wear Behavior of It—Microstructure Model-Based Analysis Approach - Anitha Kumari Azmeera; Prakash Jadhav; Chhaya Lande (Lubricants)
In aerospace applications, engine parts, especially those around the rotor blade tips, are coated with an abradable seal, a specific material layer. Its design produces a tighter seal without harming the blades by allowing it to wear down or “abrade” somewhat when the blade tips come into contact. In turbines and compressors, this reduces gas leakage between high- and low-pressure zones, increasing engine efficiency. Abradable seals are crucial to contemporary jet engines because they enhance performance and lower fuel consumption. The materials selected for these seals are designed to balance durability and abrasion resistance under high temperatures and speeds. Metal matrix, oxide particles, and porosity are the three most prevalent phases. An ideal mix of characteristics, such as hardness and erosion resistance, determines how effective a seal is, and this is accomplished by keeping the right proportions of elements in place throughout production. The primary objective of this research is to optimize abradability by utilizing various FEM tools to simulate the rub rig test and modify testing parameters, including Young’s modulus, yield stress, and tangent modulus, to analyze their impact on the wear behavior of the abradable seal and blade. Two microstructure models (CoNiCrAlY–BN–polyester coating) were found to perform optimally at porosity levels of 56% and 46%, corresponding to hardness values of 48 HR15Y and 71 HR15Y, respectively. Changing factors like yield stress and tangent modulus makes the seal more abrasive while keeping its hardness, porosity, and Young’s modulus the same. Furthermore, altering the Young’s modulus of the shroud material achieves optimal abradability when tangent modulus and yield stress remain constant. These findings provide valuable insights for improving material performance in engineering applications. To improve abradability and forecast characteristics, this procedure entails evaluating the effects of every single parameter setting, culminating in the creation of the best abradable materials. This modeling technique seems to provide reliable findings, providing a solid basis for coating design in the future.